Does believing in different types of religion affect subjective wellbeing? Analysis of the public data of the Taiwan Social Change Survey - Ding, Yu; Huo, Weidong; Jin, Yaning (Frontiers in Psychology, 2022)
Previous studies have revealed the impact of objective material conditions and psychological factors, such as the influence of religion on subjective well-being, but have disregarded the role played by differences of religious types formed in Asian cultural and historical contexts. Against this background, the present study aims to examine the association between religious type and subjective wellbeing and its mechanisms – the mediating role of frequency of religious activity and the moderating role of urban-rural areas. This study used Taiwan Social Change Survey (TSCS) 2018 data for researching. The results show that the discrepancy in the frequency of participation in religious activity caused by different types of religious belief will influence personal wellbeing. Respondents who adhere to institutional religion have a higher frequency of participating in religious activities, which has a positive impact on subjective wellbeing. Moreover, further examination shows that urban–rural areas play an important moderating role: respondents living in urban areas are more inclined to participate in religious activities frequently to gain a sense of wellbeing.